Daur al Mawāqi’ al Iliktrūniyah fī’ ‘Amaliyah al-Tarjamah min al-Lughah al-‘Arabiyah ila al-Lughah al-Indonesia wa Fa’āliyatuha (Muqāranah bayna Bing Translator wa ChatGPT) - Khoirurrosi, Khoirurrosi; Sa'adi, Zainur Rohmah (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2024)
Purpose- This study aims to determine the effectiveness of using the Bing Translator and ChatGPT websites in translating Arabic text into Indonesian using the lyrics of the song